2008
DOI: 10.1094/mpmi-21-12-1600
|View full text |Cite
|
Sign up to set email alerts
|

The Pea Sym37 Receptor Kinase Gene Controls Infection-Thread Initiation and Nodule Development

Abstract: Phenotypic characterization of pea symbiotic mutants has provided a detailed description of the symbiosis with Rhizobium leguminosarum bv. viciae strains. We show here that two allelic non-nodulating pea mutants, RisNod4 and K24, are affected in the PsSym37 gene, encoding a LysM receptor kinase similar to Lotus japonicus NFR1 and Medicago truncatula LYK3. Phenotypic analysis of RisNod4 and K24 suggests a role for the SYM37 in regulation of infection-thread initiation and nodule development from cortical-cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 48 publications
2
75
0
11
Order By: Relevance
“…In this two-way exchange, Nod factors synthesized by rhizobia function as central signal molecules, which induce early physiological responses, gene expression, and cell division in susceptible legumes (1)(2)(3). In root cells of the legume hosts, perception is mediated by Nod factor receptors (NFRs) containing ectodomains with three lysin motif (LysM) modules and cytoplasmic serine/threonine kinase domains (4)(5)(6)(7)(8)(9). Mutant studies in the model legumes Lotus japonicus (Lotus) and Medicago truncatula (Medicago) as well as the crop legumes soybean (10,11) and pea (5,6) have shown that NFRs are required for nodulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this two-way exchange, Nod factors synthesized by rhizobia function as central signal molecules, which induce early physiological responses, gene expression, and cell division in susceptible legumes (1)(2)(3). In root cells of the legume hosts, perception is mediated by Nod factor receptors (NFRs) containing ectodomains with three lysin motif (LysM) modules and cytoplasmic serine/threonine kinase domains (4)(5)(6)(7)(8)(9). Mutant studies in the model legumes Lotus japonicus (Lotus) and Medicago truncatula (Medicago) as well as the crop legumes soybean (10,11) and pea (5,6) have shown that NFRs are required for nodulation.…”
mentioning
confidence: 99%
“…In root cells of the legume hosts, perception is mediated by Nod factor receptors (NFRs) containing ectodomains with three lysin motif (LysM) modules and cytoplasmic serine/threonine kinase domains (4)(5)(6)(7)(8)(9). Mutant studies in the model legumes Lotus japonicus (Lotus) and Medicago truncatula (Medicago) as well as the crop legumes soybean (10,11) and pea (5,6) have shown that NFRs are required for nodulation. Mutant analysis in Lotus identified two NFRs, NFR1 and NFR5, and phenotypic analysis showed that both nfr1 and nfr5 mutants are equally impaired in nodule initiation (4,5).…”
mentioning
confidence: 99%
“…У гороха P. sativum L. анализ мутантов позволил выявить три наиболее вероятных кандидата на роль рецепторов к Nod-факторам: LysM-РПК, кодируемые генами Sym10, Sym37 и K1 [1,8]. Наличие LysM-мо-тивов в LysM-РПК Sym10, Sym37 и K1 позволяет от-нести их к классу рецепторов, потенциально способных связывать Nod-факторы, поскольку эти мотивы при-сутствуют в белках, узнающих соединения, состоящие из остатков N-ацетилглюкозамина [9].…”
Section: Genetic Basis Of Ecosystems Evolutionunclassified
“…Вместе с тем анализ мутантов по генам, кодирую-щим рецепторы Sym10, Sym37 и K1, свидетельствует о необходимости этих рецепторных киназ для инициа-ции развития симбиоза [1,8]. Возможным объяснением этих данных может быть способность рецепторов свя-зывать Nod-факторы с высокой аффинностью только при формировании гомо-или гетероолигомерных ком-плексов.…”
Section: анализ связывающей способности внеклеточных доменов рецепторunclassified
“…В результате за прошедшее десятилетие с использованием анализа геномной синтении были выявлены серии ортологичных симбиотических генов у ряда бобовых культур (Kouchi et al, 2010). У гороха посевного были определены нуклеотидные последовательности симбиотических ге-нов sym7 (Dolgikh et al, 2011), sym8 (Edwards et al, 2007), sym9 (Lévy et al, 2004), sym10 (Zhukov et al, 2008), sym19 (Endre et al, 2002), sym28 (Krusell et al, 2011), sym29 (Krussel et al, 2002), sym33 (Ovchinnikova et al, 2011), sym35 (Borisov et al, 2003) и sym37 (Zhukov et al, 2008). Тем не менее, у гороха не всегда оказывается возможным клонировать ген по гомологии с модельными бобовыми, т.к.…”
Section: удк 575116unclassified